Unidade seguidora de solda do robô AIR-12 (U.U.S. AIR-12) - Klitzke, Erika (2013)
The Industry of Oil and Gas (O&G), due to market competition, seeking to minimize its costs and to increase its productivity, is always in constant technological development in areas such as extraction of oil and production of oil products, maintenance and inspection of equipment, among other technical activities. In order to promote training of human resources for this industry there were created special educational programs, such as the PRHs, which are Training Programs for Human Resources that are sponsored by ANP and Petrobras. UTFPR is the seat of PRH-10, precisely the Laboratory of Automation and Advanced Control Systems (LASCA) develops projects in partnership with Petrobras and provides scholarships for students, as the members of this working group, to form human resources for industry Oil and Gas by conducting research and development projects. Among these projects tools are being developed to control and automate processes for O&G, which apply primarily to fields related to surveillance and security of equipment, foremost among these equipment there are tanks and spheres for fuel storage. These large facilities require constant maintenance. This project is characterized by the development of a module for image processing in real time, using an algorithm that defines the trajectory of a robot inspection on a tank or storage sphere. This processing is realized by hardware, and causes the robot to autonomously move along a weld bead. It was assembled a structure that allows laser to beam a weld bead and a camera performs the image capture of the light pattern formed by laser stripes on the weld bead. This image is processed by a circuit coded in VHDL (Very High Speed Integrated Circuit Hardware Description Language), which is embedded in an FPGA (Field-programmable gate array). This module is part of the control loop of the engines that perform the movement of the robot. From this module, other groups of PRH-10 scholars can develop specific inspection or location modules, so the entire robot shall become a product applicable to O&G industry.